(untitled) (Colombia Medica, 2018)
Introduction: In Colombia, 20%-54% of the population with sexual practices at higher risk for HIV infection (men who have sex with men, transgender women, women sex workers) has sometime been tested. Objective: To describe perceptions of sexual risk, HIV and HIV testing in people with risky sexual practices and people who identify themselves as heterosexual. Methods: Between 2012 and 2014, it was carried a descriptive study using HIV screening out in Cali-Colombia with the voluntary participation of 940 people aged over 18 years. There were used: informed consent, structured questionnaire and HIV testing. Descriptive, bivariate and multivariate Poisson regression models were performed. Results: Average age 28.5 ±10.9 years; 50% men. 357 (38%) were people from the traditional risk group for HIV infection; and 583 (62%) corresponded to the non-traditional risk group (heterosexual men and women). Likewise, 62% and 41% respectively had HIV test. 51% to 53% reported having sex when they consumed liquor; commercial sex was higher in the group with risky sexual practices (32% vs 3%), as well as anal relations (77% vs 23%), consistent use of condom (32% vs 9%), and HIV positive test (14.3% vs 1.6%). The multivariate analysis showed for both groups that having HIV test was associated with being older than 25 years and a history of sexually transmitted infection. Conclusions: Differentiated education strategies are needed based on risky sexual behaviors and that consider the importance of regular HIV tests for early diagnosis and timely enrollment in care and treatment.